Analisis Efektivitas Penerimaan Retribusi Pengujian Kendaraan Bermotor Dan Kontribusinya Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Dharmasraya - Mira Dwi Yanti; Elsa Fitri Amran (IAIN BATUSANGKAR, 2021)
The purpose of this study is to determine the level of effectiveness of motor vehicle testing retribution receipts and their contribution to increasing local revenue (PAD) in Dharmasraya district. This research uses descriptive methods with quantitative approaches, data collection techniques through interviews and documentation. The data analysis method used refers to the theory and formula for effectiveness and contribution. The results of this study show that the effectiveness of the acceptance of motor vehicle testing levies from 2016-2020 fluctuated or fluctuated. In 2016 the criteria for effectiveness were less effective, and in 2017 the criteria for effectiveness were quite effective, and in 2018 the criteria for effectiveness were quite effective, and in 2019 has ineffective effectiveness criteria. And in 2020 it has very effective effectiveness criteria. and the contribution of motor vehicle testing levies to local revenue In Dharmasraya Regency, the contribution levels from 2016-2020 are all classified as very less contributing, because from 2016-2020 the percentage of contribution to motor vehicle testing levies is below 10%. In 2016 the percentage of contribution was 0.41%, in 2017 it was 0.36%, in 2018 it was 0.43%, in 2019 it was 0.38% and in 2020 the percentage contribution was 0.39%.